Dietary mistakes of Polish athletes in relation to the frequency of consuming foods recommended in the Swiss food pyramid for active people - Barbara Frączek; Maria Gacek; Aleksandra Pięta; Florentyna Tyrała; Paulina Mazur-Kurach; Ewa Karpęcka (National Institute of Public Health - National Institute of Hygiene, 2020)
Background. Mistakes in dietary choices and an unbalanced diet reduce the exercise capacity of athletes. Nutritional behaviours are conditioned by environmental and individual factors. Objective. The aim of the study was to assess the scale of improper eating behaviours among high-performance Polish athletes depending on gender, sports level and type of discipline. Material and methods. The study was conducted among 610 athletes (391 men and 219 women). The group consisted of 289 athletes of individual disciplines and 321 team sports athletes representing the championship sports class (282 individuals) as well as the first and second classes (328 subjects). The authors' validated nutritional behaviour questionnaire was used, referring to the recommendation of the Swiss nutrition pyramid for athletes. In statistical analysis, the Chi2 test was applied (α=0.05). Results. Athletes most often demonstrated improper behaviours regarding: insufficient frequency of consuming vegetable fats (61.78%), fruits (59.89%), wholegrain products (59.90%), vegetables (53.62%) and dairy products (52.09%), and not limiting the intake of energy drinks (59.89%). Compared to women, men, to a larger extent, did not include the following in their daily diet: raw vegetables (p<0.001), wholegrain products (p<0.05) and vegetable fats (p<0.01). Significantly more often, they also did not limit the consumption of: animal fats (p<0.001), sweetened carbonated beverages (p<0.001), energy drinks (p<0.05) or fast food products (p<0.001). Women consumed meals less regularly (p<0.01), rarely ate fish (p<0.01), and were more likely to be inadequately hydrated (p<0.05). Athletes training individual sports disciplines compared to those training team sports consumed hydrating beverages (p<0.001) less often, but included fruit in their daily diet more frequently (p<0.05). Athletes from the master class consumed meals irregularly (p<0.01) in a smaller percentage than athletes with a lower sports class, not limiting animal fats (p<0.05) and implementing inadequate hydration (p<0.05). Conclusions. The scale of incorrect nutrition choices among athletes indicated variations depending on gender, sports level and type of sport practiced, with incorrect behaviours more often presented by men than women and competitors with a lower sports level (non-master class). The nature of the performed discipline was a factor less differentiating the nutritional choices of athletes.